Osteomyelitis in a General Pediatric Ward - Mafalda Casinhas Santos (José de Mello Saúde, 2021)
INTRODUCTION: Pediatric acute osteomyelitis (AO) is a serious condition and a challenging diagnosis. It mainly affects previously healthy individuals and Staphylococcus aureus is the leading causative agent. The objective of this study was to characterize all pediatric AO cases admitted to a second-level hospital during a six-year period. METHODS: Retrospective single-center study, including all children under 18 years-old with a primary diagnosis of AO. Descriptive statistics analysis was performed. RESULTS: Ten cases were identified, 60% males. The median age was 6.7 years. Previous trauma was referred by five. Affected locations were foot (n=3), tibia (n=3), femur (n=2), sacrum (n=1) and hand (n=1). All presented with local pain and limping or inability to walk (except one case with hand involvement). Four patients had fever and inflammatory signs, namely erythema and edema, were reported by four. At admission, nine had elevated inflammatory markers and six out of eight had normal radiographs. Magnetic resonance imaging confirmed the diagnosis in seven. Blood cultures were positive for Staphylococcus aureus (n=3) and Streptococcus pyogenes (n=1). Salmonella enteritidis was isolated from pus (n=1) and there was one presumed Kingella kingae AO defined as a positive polymerase chain reaction test from an oropharyngeal swab. The average duration of parenteral and oral antibiotherapy was 14.7 days 3.9 weeks, respectively. The antibiotic of choice was flucloxacillin. Two patients developed local complications. DISCUSSION: An unspecific and subacute clinical and radiological presentation together with low positive blood culture rates difficults timely diagnosis and management. An early empirical parenteral antibiotherapy is mandatory, followed by an oral regimen for at least four weeks.